Opening the Book. Issue 2 (3rd April 2017) - Bulock, Chris; Watkinson, Charles
ABSTRACT: Open access book publishers often face different challenges than their counterparts in journal publishing. In particular, the funding models and discovery solutions that work for journal articles may not always function as well for books. Charles Watkinson of the University of Michigan Press answered questions about recent activities in these two areas. University of Michigan Press has participated in Knowledge Unlatched, a platform that allows a large network of libraries to financially support the open access publication of books from several publishers. In order to enhance discovery of these titles and learn more about their use, the press has also begun participating in the new Open Access eBooks on JSTOR program.